Online communication satisfaction towards the use of internet-based information management systems: a study at four research universities in Malaysia - Mohd Azul Mohamad Salleh (Universiti Kebangsaan Malaysian, 2014)
Information and communication technology (ICT) now provides the means for more interactive and collaborative forms of participation in organizations. The growth of the Internet and Web 2.0 has led to a rapid development of online systems in organizations, where often the first domain to be designed has the priority aim of enhancing organizational communications processes within the area of staff interaction. Adapting the communication satisfaction and Technology Acceptance Model (TAM), the study examines online communication satisfaction in using an Internet-based information management systems (IBIMS). Its findings on the effect of ease of use and usefulness on communication satisfaction are based on a survey of 223 employees at four research universities in Malaysia. The results indicate that there is a positive and significant relationship between these variables in using IBIMS. The study contributes to an enhanced understanding of how organizations might better achieve strategic and effective communication by considering ease of use and communication satisfaction in their choice and implementation of online systems.